Geomorphologic feature and its tectonic significance in the middle and upper reaches of Yunnan section of the Lancang River Basin - Li, Sheng; Qing, Yuanhua; Li, Na; Lu, Nannan; Yang, Shuang; Xu, Yufan; Liu, Jingnan; Liu, Ruotong; He, Hao (Frontiers in Earth Science, 2025)
This paper extracted the fifth-level river system and 158 sub-basins in the middle and upper reaches of the Yunnan section of the Lancang River based on the ASTER GDEM data with a resolution of 30 m and ArcGIS software. By calculating relief, slope, hypsometric integral (HI), basin shape index (BS), stream length-gradient index (SL), and geomorphic information entropy of each sub-basin, and comprehensively considering rainfall, rock strata, and tectonics, this paper discusses the geomorphic features and tectonic significance of the middle and upper reaches of the Yunnan section of the Lancang River Basin. The research shows that: The middle and upper reaches of Yunnan section of the Lancang River Basin is in its middle age. The sub-basin shapes are mainly circular and square. The secondary river systems in the upper reaches are in the vertical drainage stage, while the secondary river systems in the middle reaches are still in the longitudinal drainage stage. The distributions of relief, slope, HI, SL, and BS are mainly controlled by tectonic activities, and the influences of rock strata and rainfall on the geomorphology are limited. In the areas of Jianchuan-Eryuan-Yangbi-Dali and the southern section of the middle reaches of the Lancang River, the tectonic uplift has stagnated and evolved into the erosion-deposition stage. The southern part of Deqin County and the southern part of Weixi County are in the uplift stage, while the tectonic uplift in the areas of Yunlong-Yongping-Luning has entered the attenuation stage. In the study area, the activity intensities of the Lanping-Yongping fault and the Weixi-Qiaohou fault are higher in the northern section and lower in the southern section. The Lancangjiang fault has a low activity intensity at the “S”-shaped big bend, while the tectonic activity in the northern section is strong. However, the tectonic activity in the southern section of the Longpan-Qiaohou fault and the northeastern section of the Nantinghe fault are weak. On the whole, the fault within the region have a controlling effect on the flow direction of the main river channel, and the patterns of the river system and the flow direction of the river channel are macroscopic responses to the tectonic uplift and lateral deformation.